Integrating Version Control in a Standardized Service-Oriented Tool Chain - Lednicki, Luka; Sapienza, Gaetana; Johansson, Morgan E.; Seceleanu, Tiberiu; Hallmans, Daniel (Proceedings - International Computer Software & Applications Conference, 2016)
The complexity of modern embedded systems most often requires multiple specialized tools to be used during the development process. These tools are commonly integrated into tool chains. An efficient way of achieving such integration is through the use of an tool integration framework, with one of the most prominent of such frameworks being Open Services for Lifecycle Collaboration (OSLC). However, at present time OSLC does not provide an established way for fully integrating version control systems. This paper presents how version control systems can be integrated into a tool chain based on OSLC. The integration is enabled by defining a version control domain based on the OSLC core specification, describing how to represent versioned artifacts and perform version control operations. The proposed approach is implemented and its feasibility is proven on a case study tool chain, which integrates the Team Foundation Server version control system and an industrial design tool for the power distribution domain.